Consumer Health Information Literacy: The Librarian’s View - Aboyade, W. A.; Asubiojo, B.O.; Ajayi, N. A. (MiddleBelt Journal of Library and Information Science, 2013)
The aim of the paper is to investigate the practice of health information literacy among the patients receiving treatment on Rheumatoid arthritis and to explore the role of medical librarian in the annals of health information literacy. As there is paucity of literature on health literacy in Nigeria, this paper will help inform discussion/research on the state of HIL of Nigerians, whether health professionals and health consumers are knowledgeable of HIL. The study involved identifying 15 patients out of 19 receiving treatment, sought their consent, collected some personal data and elicited information, through the use of interview with a set of questions that related to their health condition and information. The paper finds out that adequate health information literacy is important and necessary to patients’ partnership and participation in the decision-making process and for effective health care. This paper has significant implications for health literacy programmes in Nigeria, as it is clear that both written and oral (listening) health information delivery are preferable. However, a range of access, resources, and skills barriers prevent health care givers from fully engaging in, and benefitting from the intervention. The paper has significant implication for further research on other health related matters.